Personal and National Narratives: Systemic Functional Linguistic Analysis of 'I' and 'We' in the Biden’s Presidential Campaign - Habiba Al Umami (Bulletin of Science Education, 2024)
This study delves into Joe Biden's use of the personal pronouns "I" and "We" in his presidential campaign speeches, analyzed through the framework of Systemic Functional Linguistics (SFL). By examining how Biden presents himself and the nation, the research uncovers the narratives crafted to promote a sense of unity and leadership. The SFL framework provides a detailed description of the linguistic choices that shape Biden's self-representation and his depiction of America, highlighting the strategies used to connect with voters on both personal and national levels. The results reveal Biden's portrayal of America, his vision for the future, and the specific policies he advocates. Such portrayals are expressed through six processes of Ideational metafunction: Material, Mental, Behavioral, Verbal, Existential, and Relational. Relational process is the highest process found in the data. It implies Biden’s inclusivity as common American people and his effort to resonate with a diverse audience. In short, this analysis enhances the understanding of the rhetorical tools utilized in political discourse to create impactful narratives.